Combined Oxidative and Non-oxidative Dehydrogenation of n-Butane Over VOX Species Supported on HMS - Setnička Michal; Čičmanec Pavel; Tvarůžková Eva; Bulánek Roman (Springer, 2013)
The combination of oxidative and non-oxidative dehydrogenation of n-butane as an attractive possibility for production of C-4 olefins was studied over VOX based catalyst. Long-term activity and selectivity to desired products could be achieved over the catalysts with well dispersed monomeric vanadium oxide species supported on mesoporous silica support.
Kombinovaná oxidativní a ne-oxidativní dehydrogenace n-butanu pomocí VOX částic nanesených na HMS
Keywords: vanadium oxide; oxidative dehydrogenation; lean-oxygen conditions; n-Butane; hexagonal mesoporous silica; oxid vanadu; oxidativní dehydrogenace; n-butan; hexagonální mezoporézní silika